A study of disclosure by Singapore and Malaysian banks. - Kwan, Mark Kar Leong. (2008)
In our report, we study the reasons for the lack of disclosure by Singapore banks, and compare the differences in financial reports between Singapore and Malaysian banks. We will also provide an analysis of the reasons behind the disclosures.